2021
DOI: 10.3390/ijms22062919
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Investigation of Trifluoperazine as a Novel Therapeutic Agent for the Treatment of Pulmonary Arterial Hypertension

Abstract: Trifluoperazine (TFP), an antipsychotic drug approved by the Food and Drug Administration, has been show to exhibit anti-cancer effects. Pulmonary arterial hypertension (PAH) is a devastating disease characterized by a progressive obliteration of small pulmonary arteries (PAs) due to exaggerated proliferation and resistance to apoptosis of PA smooth muscle cells (PASMCs). However, the therapeutic potential of TFP for correcting the cancer-like phenotype of PAH-PASMCs and improving PAH in animal models remains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…The administration of TFP in two experimental rat models (Monocrotaline-and Sugen/hypoxia-induced PAH) significantly lowered RVSP, diminished total pulmonary resistance, decreased the medial wall thickness of distal pulmonary arteries, and improved RV function. Overall, these data indicate that TFP might provide beneficial effects for the treatment of PAH and support the notion that finding new applications for old medications could be a very productive approach [7].…”
supporting
confidence: 69%
“…The administration of TFP in two experimental rat models (Monocrotaline-and Sugen/hypoxia-induced PAH) significantly lowered RVSP, diminished total pulmonary resistance, decreased the medial wall thickness of distal pulmonary arteries, and improved RV function. Overall, these data indicate that TFP might provide beneficial effects for the treatment of PAH and support the notion that finding new applications for old medications could be a very productive approach [7].…”
supporting
confidence: 69%
“…28 In addition, in support of the prevailing model of PAH development, that is, initial apoptosis of PA endothelial cells followed by extensive proliferation of adjacent PA smooth muscle cells (PASMCs) and apoptosis-resistant PA endothelial cells, 29 the development of the rat Su/ hypoxic (Su/Hx) model represents a significant advance providing a complementary alternative to the MCT rat model. Indeed, due to its ability to cause severe and irreversible PH with the appearance of angio-obliterative lesions, the Su/Hx rat model (while certainly not without criticism) has become one of the most used preclinical models of PAH with therapeutic intervention initiated at either 3 weeks (immediately after the end of hypoxia exposure) or 5 to 8 weeks (after 2-5 weeks of normoxic recovery) post-Su injection 26,[30][31][32] (Figure 1). More recently, the rat Su/Hx model was adapted to mice 33 to take benefit of existing genetically modified mice and thus gain mechanistic insights into the pathogenesis of PAH.…”
Section: Sugen/hypoxiamentioning
confidence: 99%
“…Moreover, the authors observed a dose‐dependent increase in LC3‐II level, which indicates autophagosome accumulation. An immunofluorescence analysis confirmed the accumulation of cytoplasmic LC3‐positive dots after trifluoperazine treatment (Grobs et al, 2021).…”
Section: The Impact Of Phenothiazine Derivatives On Autophagymentioning
confidence: 83%
“…The impact of trifluoperazine (5 and 10 μM) on autophagy of pulmonary artery smooth muscle cells with pulmonary arterial hypertension (PAH‐PASMCs) cells was analyzed by Grobs et al (2021). The bright‐field phase‐contrast microscope analysis showed an accumulation of small and large vesicle‐like structures, which is a feature typically observed in autophagy.…”
Section: The Impact Of Phenothiazine Derivatives On Autophagymentioning
confidence: 99%
See 1 more Smart Citation